Extinction procedure induces pruning of dendritic spines in CA1 hippocampal field depending on strength of training in rats - Garín-Aguilar, María E.; Díaz-Cintra, Sofía; Medina, Andrea C.; Quirarte, Gina L.; Aguilar-Vázquez, Azucena; Prado-Alcalá, Roberto A. (Frontiers in Behavioral Neuroscience, 2012)
Numerous reports indicate that learning and memory of conditioned responses are accompanied by genesis of dendritic spines in the hippocampus, although there is a conspicuous lack of information regarding spine modifications after behavioral extinction. There is ample evidence that treatments that typically produce amnesia become innocuous when animals are submitted to a procedure of enhanced training. We now report that extinction of inhibitory avoidance, trained with relatively low foot-shock intensities, induces pruning of dendritic spines along the length of the apical dendrites of hippocampal CA1 neurons. When animals are trained with a relatively high foot-shock there is a high resistance to extinction, and pruning in the proximal and medial segments of the apical dendrite are seen, while spine count in the distal dendrite remains normal. These results indicate that pruning is involved in behavioral extinction, while maintenance of spines is a probable mechanism that mediates the protecting effect against amnesic treatments produced by enhanced training.